How to Listen Through a Wall: Lessons From Conducting Participatory Action Research in an Urban Prison - Rell, Emalie (Journal of contemporary criminal justice, 2024)
This project sought to understand the present-day experiences of individuals housed in prisons by utilizing Participatory Action Research (PAR) methods that partnered a university research team with individuals incarcerated in an urban correctional facility. The team assessed perceptions of the current environment by surveying people incarcerated in an urban prison. This article discusses the role of PAR methodologies from project initiation to finalization, explicitly focusing on coordination with prison and Department of Correction (DOC) administrative leadership and the value of including incarcerated individuals on the research team for successful change. Throughout the process, the team identified areas for improvement and innovations to improve the prison environment. This article provides a road map, lessons learned from conducting PAR in prison environments, and the power of partnering researchers and members of the researched population on one collaborative research team.